Teknik Perbanyakan Cepat Sumberdaya Genetik Iles-Iles Untuk Mendukung Percepatan Komersialisasi Secara Berkelanjutan - Edi Santosa; Desta Wirnas (Jurnal Ilmu Pertanian Indonesia, 2009)
Increasing demand on glucomannan as healthy diet in develop countries, promotes higher planting area of Amorphophallus. Iles-iles corm (Amorphophallus muellen) contains high percentage of glucomannan. In order to meet with increasing demand, providing mass planting materials is a great concern in Indonesia. Therefore, the study on skin corm and bulbil as propagation materials was conducted. In the first experiment, bulbil with different size and section, i.e., very small, small, medium and large, and half section and 1f4 section were used. In the second experiment, we evaluated the prospect of skin corm as propagul where different size of skin corm was used, i.e., 1 em x 1 em, 2 em x 2 em, and 4 em x 4 em. Results showed that both bulbil and skin corm could be utilized as prospectivepropagules of iles-iles. Propagation using bulbil was more superior as compared to skin corm. Bulbil of both whole and sectioned had high emergence of bud (> 90%), except very small sized ones. Very small bulbil (diameter less than 1 em) resulted in ca 605 of emergence. Skin corm sized 4 em x 4 em produced equal emergence to medium bulbil. In general, increasing size of skin corm increased success of emergent bud. Delaying emergence on small sized skin corm could be assessed by smaller nutrient reserved. Most unseccessemergence of small sized skin and very small bulbil was due to decay of the propagules. These experiments implied that both bulbils and skin corm could be used as mass propagules for iles-iles production.